Gender in livestock development: Jimmy Smith - Smith, Jimmy W. (International Livestock Research Institute, 2019)
Jimmy Smith, ILRI director general, shares his ‘aha’ moment when he really understood the central importance of women in livestock development. This film was produced to mark the International Women’s Day 2019 which is themed ‘Think equal, build smart, innovate for change’.